Parental influence and perceptions on youth single sport specialization: a systematic review - Haider, A. A.; Troyer, S. C.; Mologne, M. S.; Hardi, A.; Kuhn, A. W. (The Physician and Sportsmedicine, 2024)
Objective To evaluate the role of parental influence on youth SSS and to characterize parental perceptions of SSS.